Salt templated synthesis of hierarchical covalent triazine frameworks - Troschke, Erik; Graetz, Sven; Borchardt, Lars; Haubold, Danny; Senkovska, Irena; Eychmueller, Alexander; Kaskel, Stefan (Microporous and Mesoporous Materials, 2017)
Covalent triazine framework (CTF-1) materials with hierarchical pore structures have been synthesised using a salt templating approach. As salt templates binary mixtures of ZnCl2 with various alkali chlorides (instead of only ZnCl2) in combination with a modified temperature protocol were utilised. The porosity of salt templated CTF-1 materials was analysed by means of argon physisorption at 87 K. In addition to microporosity, typical for CTF-1, the resulting materials show enhanced mesoporosity and have high total pore volumes of up to 2.1 cm3 g−1. The presented synthetic protocol provides an access to materials combining high nitrogen content, hierarchical pore structure, and high total pore volume, while established CTF syntheses at elevated temperatures used to increase the pore volume in general cause nitrogen loss. These new hierarchical CTFs are very promising cathode materials for lithium-sulphur batteries, where both characteristics (nitrogen content and mesoporosity) are crucial.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Argon physisorption; Mesoporous materials; Porous polymers; Salt templating